CONGLOMERATE SPIN-OFFS: WHETHER U.S. TAX LAW INHIBITS DECONGLOMERATION - Maxey, Bryce (Columbia Journal of Tax Law, 2022)
In this Note, I examine whether the complex nature of the U.S. spin-off rules and the burdens associated with successfully navigating such rules discourage conglomerates from breaking up into smaller companies through tax-free spin-offs. First, I argue that there are numerous disadvantages of conglomeration, which generally tend to outweigh any economic benefits derived from the conglomerate form. Next, I describe the statutory and nonstatutory requirements of tax-free spin-offs, evaluating particularly how each requirement may impact a conglomerate wishing to spin off one or more of its business units. Because conglomerates are usually multinational corporations, I also briefly consider the tax consequences of spinning off a foreign company. In the following section, I discuss the issuance of private letter rulings in connection with conglomerate spin-offs and assess whether the I.R.S.’s recent policy changes have accelerated spin-off activity or, to the contrary, whether they have produced a chilling effect on conglomerate spin-offs. Finally, I examine a recent example of a successful conglomerate spin-off—Liberty’s spin-off of TripAdvisor—before analyzing an example of a failed conglomerate spin-off—Yahoo’s attempt to spin off Alibaba. I conclude that, although tax-free spin-offs are occasionally unsuccessful, such failures are rare. Even if the tax rules are byzantine and the monetary stakes are exceptionally high, conglomerates wishing to spin off business units typically manage to satisfy the requirements. Therefore, although U.S. tax law does not completely hinder deconglomeration, spin-offs are nevertheless costly. Fulfilling the spin-off requirements leads to economic inefficiencies because it entails expensive pre-spin-off restructuring and delays, as well as high transaction and friction costs.